2017
DOI: 10.1002/srin.201600469
|View full text |Cite
|
Sign up to set email alerts
|

Evolution on Topography of Textured Work Rolls and Steel Strips during Cold Rolling and Temper Rolling

Abstract: In this paper, topography characteristics are statistically analyzed based on a large number of field measured data to investigate the roughness failure on textured work rolls and the evolution on steel strips during cold rolling and temper rolling. It is revealed that the height distribution in the surface profile of steel strips is barely influenced by the skewed height distribution in the surface profile of work rolls. The roughness of steel strips is efficiently improved by the last stand of cold rolling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Note also that the height of the deviation peaks is attenuated in the current pass. References [8,19,33,34] show similarly that roughness of the strip decreases after a rolling pass employing smooth rolls. From Fig.…”
Section: Work Roll Bending As Corrective Mechanismmentioning
confidence: 93%
“…Note also that the height of the deviation peaks is attenuated in the current pass. References [8,19,33,34] show similarly that roughness of the strip decreases after a rolling pass employing smooth rolls. From Fig.…”
Section: Work Roll Bending As Corrective Mechanismmentioning
confidence: 93%
“…Temper rolling (skin-pass rolling) is the rolling process used in the final forming stage of automotive sheets [4]. In the temper rolling process, the surface roughness profile is transferred to the materials through rolls with a special texture [5]. Thanks to the surface roughness profile obtained, the forming ability and paint adhesion of sheet materials are improved.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are rolling speed, elongation, reduction ratio, properties of the material, roll parameters (roughness, radius, material, roughening method), lubrication conditions, etc. (Wu et al , 2019; Xia et al , 2017; Rodriguez-Vidal et al , 2020; Kijima, 2014; Mekicha et al , 2020; Nagase et al , 2009a; Köhler et al , 2016). Dick and Lenard (2005) concluded that as the rolling speed increased, loads and a forward slip would increase, thereby increasing the surface roughness of the sheets and approaching the value of the roll roughness.…”
Section: Introductionmentioning
confidence: 99%